Comprehensive characterization of ureagenesis in the spfash mouse, a model of human ornithine transcarbamylase deficiency, reveals age-dependency of ammonia detoxification - Allegri, Gabriella; Deplazes, Sereina; Rimann, Nicole; Causton, Benjamin; Scherer, Tanja; Leff, Jonathan W; Diez-Fernandez, Carmen; Klimovskaia, Anna; Fingerhut, Ralph; Krijt, Jakub; Kožich, Viktor; Nuoffer, Jean-Marc; et al. (Journal of inherited metabolic disease, 2019)
The most common ureagenesis defect is X-linked ornithine transcarbamylase (OTC) deficiency which is a main target for novel therapeutic interventions. The spf ash mouse model carries a variant (c.386G>A, p.Arg129His) that is also found in patients. Male spf ash mice have a mild biochemical phenotype with low OTC activity (5%-10% of wild-type), resulting in elevated urinary orotic acid but no hyperammonemia. We recently established a dried blood spot method for in vivo quantification of ureagenesis by Gas chromatography-mass spectrometry (GC-MS) using stable isotopes. Here, we applied this assay to wild-type and spf ash mice to assess ureagenesis at different ages. Unexpectedly, we found an age-dependency with a higher capacity for ammonia detoxification in young mice after weaning. A parallel pattern was observed for carbamoylphosphate synthetase 1 and OTC enzyme expression and activities, which may act as pacemaker of this ammonia detoxification pathway. Moreover, high ureagenesis in younger mice was accompanied by elevated periportal expression of hepatic glutamine synthetase, another main enzyme required for ammonia detoxification. These observations led us to perform a more extensive analysis of the spf ash mouse in comparison to the wild-type, including characterization of the corresponding metabolites, enzyme activities in the liver and plasma and the gut microbiota. In conclusion, the comprehensive enzymatic and metabolic analysis of ureagenesis performed in the presented depth was only possible in animals. Our findings suggest such analyses being essential when using the mouse as a model and revealed age-dependent activity of ammonia detoxification.
Keywords: Liver; Animals; myši transgenní; urea cycle disorders; Ammonia; age-dependency; hyperamonemie; hyperammonemia; játra; močovina; Age Factors; Mice, Transgenic; Hyperammonemia; Aging; věkové faktory; ornithine transcarbamylase (OTC) deficiency; lidé; Mice; spfash mouse model; ureagenesis; myši; ornithinkarbamoyltransferasa; nemoc z nedostatku ornithinkarbamoyltransferázy; Ornithine Carbamoyltransferase; Male; modely nemocí na zvířatech; Ornithine Carbamoyltransferase Deficiency Disease; stárnutí; Disease Models, Animal; zvířata; mužské pohlaví; gut microbiome; amoniak; Urea; Humans